Taking the bait understanding Filipino Generation Z’s meaning-making of foreign-produced video blogs on Philippine culture. - Garcia, John Mark Diwa
The widespread emergence of the Pinoybaiting phenomenon is described as a localized pursuit of Western producers through video blogs (vlogs) to exploit the country's cultural appurtenances to amass Filipino audiences for economic gain.